RANCANGAN APLIKASI MONITORING PRODUKSI DAN PENGIRIMAN DENGAN METODE SHORTAGE DI PT. INDAH KIAT PULP & PAPER SERANG MILL TBK - Kania Kania; Ely Nuryani; Azwarsyah Azwarsyah (Program Studi Sistem Informasi, Universitas Banten Jaya, 2019)
Design of production and delivery monitoring applications at PT. Indah Kiat Pulp & Paper Serang Mill Tbk aims to reduce problems in the production control process. The problems faced are as follows; the production process carried out by several parts results in slow processing of products, often duplicate data orders that can harm the company, the production of damaged products is not recorded, the number of reprimands from customers due to delay in delivery time due to ordering deficiencies the company must reset the production schedule. Based on these problems computer-based method (IT) shortage is needed. System design uses the waterfall method or SDLC (System Development Life Cycle). Software modeling uses UML (unified model language). The application has advantages such as the more structured and well-documented because the procedure is in accordance with the rules made by the Converting Division at PT. Indah Kiat Pulp & Paper. This application is expected to be able to overcome all existing constraints, especially in managing production data. Based on the things mentioned above, the authors are interested in compiling articles about the design of Production and Delivery Monitoring Applications with the Shortage Method at PT. Indah Kiat Pulp & Paper Serang Mill Tbk.